In Silico Study of Liquid Smoke Rice Husk against COVID-19 - Arundina, Ira; Frimayanti, Neni; Surboyo, Meircurius D. C.; Budhy, Theresia I.; Iskandar, Benni; Pradana, Arya; Rahmaputry, Tytania (European Journal of Dentistry, 2022)
Objectives Liquid smoke rice husk has been researched and proved to consist of antibacterial, analgesic, anti-inflammatory, and growth factor stimulatory properties. By these complex properties, the liquid smoke rice hull is able to purpose as a novel coronavirus disease 2019 (COVID-19) inhibitor. The research was conducted to analyze the role of the dominant compound in rice husk liquid smoke against one of the main proteases in complex with inhibitor N3 of COVID-19 and 6LU7 protein data bank (PDB) ID.Materialand Methods The Molecular Operating Environment (MOE) 2020.0901 (Chemical computing group) was used to analyzed the interaction. The molecular structure test, including phenol, mequinol, 2-methoxy-phenol, 6-octadecenoic acid, oleic acid, 9-cctadecenoic acid, was chosen. The lopinavir as positive control and 6LU7 as COVID-19 protein were chosen. All the protein analyses were conducted using docking molecular.Result The phenol, 2-methoxy-phenol, mequinol and 9-octadecenoic acid have higher binding free energy that causes difficult to bind to the active site of protein 6LU7 (−3.4758, −3.5509, −3.6845, and −5.0173 kcal/mol, respectively). The minor component of liquid smoke, such as 6-octadecenoic acid and oleic acid, has the binding free energy (−5,5327 and −5,4208 kcal/mol) and more factor of binding presumably as active COVID-19 inhibitor.Conclusion The liquid smoke rice husk has active component like 6-octadecenoic acid and oleic acid are presumably as active COVID-19 inhibitor.
Keywords: liquid smoke; rice husk; coronavirus disease 2019; infectious disease; in silico